Information, financial aid and training participation: Evidence from a randomized field experiment - Katja Görlitz; Marcus Tamm (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2016)
To increase employee participation in training activities, the German government introduced a large-scale training voucher program in 2008 that reduces training fees by half. Based on a randomized field experiment, this paper analyzes whether providing information about the existence and the conditions of the training voucher had an effect on actual training activities of employees. Because the voucher was newly introduced, only one-fourth of the eligible employees knew the voucher exists at the time of the experiment. The information intervention informed a random sample of eligible employees by telephone about the program details and conditions. The results indicate that the information significantly increased treated individuals' knowledge of the program but had no effect on voucher take-up or participation in training activities. Additional descriptive analyses suggest that the reasons for these zero effects are that the demand for self-financed training is low and that liquidity constraints do not discourage many employees from training participation. – – Im Jahr 2008 wurde in Deutschland das Programm Bildungsprämie eingeführt. Mit diesem Weiterbildungsgutschein, der eine 50-prozentige Erstattung der Weiterbildungskosten umfasst, sollen Erwerbstätige zu Weiterbildung angeregt werden. Anhand eines randomisierten Feldexperiments untersucht die Studie, ob ein verstärktes Bekanntmachen des Gutscheins mittels einer 'Informationsintervention' zu Änderungen im Weiterbildungsverhalten von Erwerbstätigen führt. Da der Gutschein erst kürzlich eingeführt wurde, war die Bekanntheit zum Zeitpunkt des Feldexperiments vergleichsweise gering. Die Ergebnisse zeigen, dass die Informationsintervention die Bekanntheit der Bildungsprämie signifikant erhöht hat, die Teilnahme an Weiterbildung hierdurch jedoch nicht verändert wurde. Ergänzende Analysen legen nahe, dass der fehlende Einfluss auf die Weiterbildungsteilnahme auf eine insgesamt geringe Nachfrage nach eigenfinanzierter Weiterbildung zurückzuführen ist sowie auf den Umstand, dass finanzielle Beschränkungen nur wenige Erwerbstätige von Weiterbildung abhalten und die Behebung dieser finanziellen Beschränkungen daher kaum Wirkung entfaltet.
Keywords: I22; D83; H52; 330; training participation; voucher; financial aid; randomized field experiment; information treatment